Game Method of Rehabilitation of Children with Infantile Cerebral Paralysis - Malika T. Egamova1, Nasiba K. Murtazaeva1, Salomat A. Halimova1, Adiba A. Usmankhodzhaeva2, R.Zh. Ma (Indian Journal of Forensic Medicine & Toxicology, 2020)
Nowadays, the problem of the vital functions of patients with infantile cerebral paralysisis in the combinationof various aspects of rehabilitation: rehabilitation and recreation, physical and psychological, social,emotional and educational. In a comprehensive rehabilitation system, more attention has been paid recentlyto new organizational forms, such as the game method.The aim of research: To develop a new rehabilitation system for children with infantile cerebral paralysis.Materials and Method: We examined 52 children aged 2 to 12 years with various forms of infantile cerebralparalysis. The control group, we were engaged in physical therapy in a game form along with mothers.Results: Children who played in a game way with their mothers improved movement in the limbs, improvedmood, enjoyed doing exercises and had a positive result more than the previous group.